PHARMACOLOGICAL PROPERTIES OF THE OINTMENT 'AS-ARVENS' BASED ON EQUISETUM RAMOSISSIMUM, EQUISETUM ARVENSIS, AND CONVOLVULUS ARVENSIS PLANTS (Scientific journal of the Fergana State University, 2025)
This article presents the pharmacological properties of the "As-Arvens" ointment obtained from the plants Equisetum ramosissimum, Equisetum arvensis, and Convolvulus arvensis. The research discusses experiments aimed at determining the antibacterial and antifungal activity of the plant-based ointment. The effect of the ointment on the healing of open wounds on the skin of mice was studied to assess its pharmacological impact.